Polypyrimidine tract‐binding protein binds to the 5′ untranslated region of the mouse mammary tumor virus mRNA and stimulates cap‐independent translation initiation. (5th April 2016) - Cáceres, Carlos J.; Contreras, Nataly; Angulo, Jenniffer; Vera‐Otarola, Jorge; Pino‐Ajenjo, Constanza; Llorian, Miriam; Ameur, Melissa; Lisboa, Francisco; Pino, Karla; Lowy, Fernando; Sargueil, Bruno; López‐Lastra, Marcelo
Abstract : The 5′ untranslated region (UTR) of the full‐length mRNA of the mouse mammary tumor virus (MMTV) harbors an internal ribosomal entry site (IRES). In this study, we show that the polypyrimidine tract‐binding protein (PTB), an RNA‐binding protein with four RNA recognition motifs (RRMs), binds to the MMTV 5′ UTR stimulating its IRES activity. There are three isoforms of PTB: PTB1, PTB2, and PTB4. Results show that PTB1 and PTB4, but not PTB2, stimulate MMTV‐IRES activity. PTB1 promotes MMTV‐IRES‐mediated initiation more strongly than PTB4. When expressed in combination, PTB1 further enhanced PTB4 stimulation of the MMTV‐IRES, while PTB2 fully abrogates PTB4‐induced stimulation. PTB1‐induced stimulation of MMTV‐IRES was not altered in the presence of PTB4 or PTB2. Mutational analysis reveals that stimulation of MMTV‐IRES activity is abrogated when PTB1 is mutated either in RRM1/RRM2 or RRM3/RRM4. In contrast, a PTB4 RRM1/RRM2 mutant has reduced effect over MMTV‐IRES activity, while stimulation of the MMTV‐IRES activity is still observed when the PTB4 RRM3/RMM4 mutant is used. Therefore, PTB1 and PTB4 differentially stimulate the IRES activity. In contrast, PTB2 acts as a negative modulator of PTB4‐induced stimulation of MMTV‐IRES. We conclude that PTB1 and PTB4 act as IRES trans ‐acting factors of the MMTV‐IRES. Abstract : The 5′untranslated region (UTR) of the full length mRNA of the mouse mammary tumor virus (MMTV), retrovirus associated to mammary tumors, harbors an internal ribosomal entry site (IRES). In this study we show that two isoforms the polypyrimidine‐tract‐binding protein (PTB); PTB1 and PTB4 stimulate MMTV‐IRES activity. We conclude that PTB1 and PTB4 act as IRES trans ‐acting factors of the MMTV‐IRES.